2015
DOI: 10.1074/jbc.m114.620369
|View full text |Cite
|
Sign up to set email alerts
|

MiR-22-silenced Cyclin A Expression in Colon and Liver Cancer Cells Is Regulated by Bile Acid Receptor

Abstract: Background: miR-22 has a tumor-suppressive effect, but its regulation remains to be characterized. Results: miR-22 is regulated by bile acid-activated FXR, and CCNA2 is a miR-22 target. Conclusion: FXR-induced miR-22 in inhibiting CCNA2 is a novel pathway for FXR to exert its protective effect in the gastrointestinal tract. Significance: The FXR-miR-22-CCNA2 axis is a novel mechanism for FXR-mediated anti-proliferative effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 35 publications
6
68
0
Order By: Relevance
“…Deregulation of cyclin A2 was associated with erroneous cell proliferation and chromosomal instability (38,39), and aberrant expression of cyclin A2 has been linked to multiple types of malignancies, including breast, liver, and lung cancers (38)(39)(40). In light of our observation that USP7-mediated deubiquitination and stabilization of PHF8 regulate the expression of cyclin A2, it is reasonable to postulate that the USP7/PHF8 signaling pathway plays a role in cell proliferation and carcinogenesis.…”
Section: Resultsmentioning
confidence: 93%
“…Deregulation of cyclin A2 was associated with erroneous cell proliferation and chromosomal instability (38,39), and aberrant expression of cyclin A2 has been linked to multiple types of malignancies, including breast, liver, and lung cancers (38)(39)(40). In light of our observation that USP7-mediated deubiquitination and stabilization of PHF8 regulate the expression of cyclin A2, it is reasonable to postulate that the USP7/PHF8 signaling pathway plays a role in cell proliferation and carcinogenesis.…”
Section: Resultsmentioning
confidence: 93%
“…Accumulating amounts of evidence suggest that miR-22-3p partcipates mainly in cell growth and differentiation. Previous studies have shown that miR-22-3p can promote CLL-B cell and cardiomyocytes proliferation [26,27]; however, in most carcinomas, including breast cancer [28], gastric carcinoma [29], medulloblastomas [30] and liver cancer [31], miR-22-3p suppressed cancer cell proliferation. Thus the biological functions of miR-22-3p in HASMCs require further study.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%
“…For example, the miR-22 shows different effects in these cancers [80][81][82][83]. DADS can silence HIF-1α (hypoxia inducible factor 1α) via increasing expression of miR-22 to repress VEGF (vascular endothelial growth factor) expression to block angiogenesis, leading to the disruption of cancer progression [79,84]. The upregulation of miR-22 induced by DADS may post-transcriptionally target cyclin A2 and CDKN1A (cyclin-dependent kinase inhibitor 1A) to arrest the cell cycle in G0/G1 phage in CRC and liver cancer cells, respectively [85,86].…”
Section: Regulation Of the Mirnas By Dadsmentioning
confidence: 99%